QSAR applications during last decade on inhibitors of acetylcholinesterase in Alzheimer's disease - Wong, K. Y. (2012)
This article reviews multi-criteria QSAR applications on Acetylcholinesterase inhibitors as palliative drugs for Alzheimer's Disease, published in the period 2001-2011. It includes QSAR models for different series of compounds, comparative studies, and advances in methodologies. This period is marked by a shift in focus from palliative treatment to pathogenesis. However, we believe that research into palliative treatment should continue. More comparative studies are desirable. In order to facilitate comparative and general studies on Acetylcholinesterase inhibitors, a standard experimental protocol for measuring an inhibitor's potency is needed. Finally, we recommend chemists to work closely with system and molecular biologists.